INFLUENCE OF SODIUM DODECYL SULFATE ON STABILITY OF BILAYER LIPID MEMBRANES - Tonoyan, L.A.; Torosyan, A.L.; Arakelyan, V.B. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2016)
In the paper influence of Sodium dodecyl sulfate (SDS) on planar bilayer lipid membranes (BLM) was investigated. It was shown that the presence of SDS and it’s concentration increasing leads to the loss of stability of the BLM, which is associated with the decrease in the value of the linear tension of pore edge in BLM, because of positive spontaneous curvature of the SDS molecule. It is also shown that the number of lipid pores on the BLM increases as a result of increase in probability of the pore formation, with reduction of the value of linear tension.
Keywords: bilayer lipid membrane, sodium dodecyl sulfate, cyclic currentvoltage characteristic, BLM stability